ANALISIS KUALITAS APLIKASI TALOCRAFT MENGGUNAKAN STANDAR ISO/IEC 25010 - Swari, Dw Ayu Agung Indra; I Ketut Dedy Suryawan; I Komang Sugiartha; Putu Julian Mahadewi; I Made Putu Darmawan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
This research aims to analyze and evaluate user satisfaction of the Talocraft application based on the four characteristics contained in ISO/IEC 25010. The four characteristics used are based on the ISO/IEC 25010 standard, namely Functional Suitability, Performance Efficiency, Usability, and Portability. The data collection methods used in this research were observation, interviews and questionnaires. The instruments used are functionality questionnaire (black box testing), USE Questionnaire, response time and cross testing. The overall results of this research are that the Talocraft application meets ISO 25010 quality standards. The functional suitability characteristic produces a score of 1 (good), which means this application has run as expected. The performance efficiency characteristic produces an average response time of 5.2 seconds, which means it meets the performance efficiency standard of less than 7 seconds (accepted). Usability characteristics were measured by distributing questionnaires to tourists and MSMEs as well as the relevant MSMEs Department and produced a score of 87.1% (very feasible). The portability characteristic is carried out by installing the Talocraft application into five different Android operating systems and producing a score of 100% (A), which means the Talocraft application runs very well on five different Android operating systems.